1999
DOI: 10.1002/(sici)1098-1136(19990115)25:2<199::aid-glia10>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

K+ channel density increases selectively in the endfoot of retinal glial cells during development ofRana catesbiana

Abstract: The radial glial cells that span the retina, described by Müller in 1851, have a remarkable distribution of ion channels in adult amphibia that mediate extracellular K+ spatial buffering. 94% of the total membrane conductance of these cells resides in inward rectifier K+ channels in the endfoot processes apposed to the vitreous humour. We now report that this regional specialization is found in Müller cells isolated from adult (>120 day old) bullfrogs but to a far less extent in those from 10–20 day old tadpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In the retina, where Mü ller cells are known to siphon K ϩ from the plexiform layers to the vitreous fluid, Kir channels are thought to mediate K ϩ influx and efflux (Newman, 1993). In rat and rabbit, the Kir channels of Mü ller cells have been identified as Kir4.1 and Kir channels have been shown by patch clamp recordings to be concentrated at the endfeet (Brew et al, 1986;Newman, 1993;Rojas and Orkand, 1999). Kofuji et al (2000) have created a Kir4.1 knockout mouse and examined the retinal Mü ller cells in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, where Mü ller cells are known to siphon K ϩ from the plexiform layers to the vitreous fluid, Kir channels are thought to mediate K ϩ influx and efflux (Newman, 1993). In rat and rabbit, the Kir channels of Mü ller cells have been identified as Kir4.1 and Kir channels have been shown by patch clamp recordings to be concentrated at the endfeet (Brew et al, 1986;Newman, 1993;Rojas and Orkand, 1999). Kofuji et al (2000) have created a Kir4.1 knockout mouse and examined the retinal Mü ller cells in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…3B). In developing amphibian Mü ller cells, a similar increase of the K IR channel density was observed that occurred selectively in the membrane of the endfeet (Rojas and Orkand, 1999). The increased K IR conductance in rabbit cells is accompanied by a hyperpolarization of the mean resting membrane potential (RMP) from Ϫ40 mV in cells from newborn animals to mean values negative to Ϫ80 mV at postnatal day (ϭP) 13 ( Fig.…”
Section: K Ir Channel Activity and Membrane Potentialmentioning
confidence: 99%
“…A typical process during postnatal maturation of Müller cells is the upregulation of Kir currents. Although most of the respective data were collected in mammals (see the chapter above), a similar process was also observed by Rojas and Orkand () by comparing tadpoles and adult frogs. A developmental increase of AQP4 and orthogonal arrays of particles has been described in the retina of rats (Wurm et al, ) and birds, respectively (Bolz and Wolburg, ).…”
Section: Comparative Aspectsmentioning
confidence: 90%
“…Some of the authors demonstrated that a large part of the K + channels (or the K + conductance) is located in the endfoot region. Rojas and Orkand () studied the density of K + channels in tadpoles and adults of Rana catesbeiana . They observed an increase of the K + conductance in the endfoot during development.…”
Section: Amphibiansmentioning
confidence: 99%